Radiotherapy in practice: Radioisotope therapy - Hoskin, Peter J (Oxford University, 2014)
Radioisotope therapy is an internal form of radiation, administered through liquid or injection that treats cancer with minimal damage to the normal surrounding tissue. This book is a practical guide to radioisotope therapy, taking the reader through the basic principles, and then developing this by application to specific sites and diseases.